MATERIAL CULTURE OF THE KARAKALPAKS: ANALYSIS AND INTERPRETATION (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The article analyzes research dedicated to the material culture of the Karakalpaks, one of the largest Turkic-speaking peoples of Central Asia. Particular attention is given to works published since 1991, the year Uzbekistan gained state independence. During this period, various aspects of the Karakalpaks' material culture, including traditional clothing, jewelry, culinary traditions, and traditional forms of housing, have been actively studied. The analysis of these studies not only deepens the understanding of the daily life and practices of the Karakalpak people but also reveals broader ethnocultural processes occurring in the region. Each of the mentioned elements of material culture serves as an important indicator of the historical evolution and cultural identity of the Karakalpaks, reflecting their traditions, customs, and values.